Early matter domination at colliders: Long live the glueball! - Fady Bishara; Filippo Sala; Kai Schmidt-Hoberg (Physics Letters B)
We prove that collider searches for long-lived particles (LLPs) can test the dynamics responsible for matter domination in the early universe. In this letter we concentrate on the specific example of glueballs from a GeV-scale confining dark sector and compute the dilution of cosmological relics induced by their decay. We then show that searches for long-lived glueballs from Higgs decays test increasing values of dilution at ATLAS and CMS, CODEX-b, ANUBIS and MATHUSLA. We identify the general features that make models of early matter domination discoverable via LLPs at colliders. Our study provides a quantitative physics motivation to test longer lifetimes.